PEMBINAAN KEAGAMAAN PADA PECANDU NARKOBA DI REHABILITASI INSTITUSI PENERIMA WAJIB LAPOR (IPWL) PONDOK PESANTREN SALAFIYAH HIDAYATUL MUBTADI-IEN KOTA BENGKULU - Hendro Cahyana (Pascasarjana UIN Fatmawati Sukarno Bengkulu, 2017)
The purpose of this study is an attempt to find out how the method of religious guidance on Drug Addicts at Pondok Pesantren Salafiyah Hidayatul Mubtadi-ien Bengkulu City. The questions to be answered through this research are: (1) How is the religious activity of santri Drug Rehabilitation Rehabilitation Center at Pondok Pesantren Salafiyah Hidayatul Mubtadi-ien Bengkulu City? (2) How is the method of religious activity applied to Drug Addicts in Pondok Pesantren Salafiyah Hidayatul Mubtadi-ien Bengkulu City? (3) What are the barriers and carrying capacity an the process of religious guidance on Drug Addicts in Pondok Pesantren Salafiyah Hidayatul Mubtadi-ien Bengkulu City